Interprofessional undergraduate students talk about nurses and nursing: A qualitative study. (April 2016) - Crawford, Ruth M.; Gallagher, Peter; Harding, Thomas; McKinlay, Eileen M.; Pullon, Susan R.
Summary: Objectives: To understand the discourse amongst a range of health professional students, including nursing, talking about nurses and nursing. Design: A qualitative descriptive study which employed the use of focus groups. Settings: A rural and residential interprofessional immersion programme in a rural location in New Zealand. The participants were final year undergraduates drawn from seven different degrees (dentistry, dietetics, medicine, nursing, occupational therapy, pharmacy and physiotherapy). Methods: Data were collected from separate and sequential group interviews; each of which comprised a different mix of students and always included nursing students. Each student participated once. Data were analysed by comparing datum with datum until recurrent themes emerged. Results: The discourse in relation to nurses and nursing identified two overarching themes 'constrained conversations' and 'the benefit of IPE: what nursing might become'. Within those themes there were four contributing sub themes; 'nursing as doing', 'limiting our vocabulary', 'becoming part of the conversation 'and 'moving from the present to the future what nursing might become'. Conclusions: The interprofessional experience for student nurses not only enabled them to learn about other professions but was a forum in which they were able to articulate the role of the nurse. This was an unintended and positive by-product of the IPE programme. Highlights: Articulating the nature of nursing prove troublesome Nursing students should be intentionally exposed to other students with the clear purpose to find out about each other's role. IPE provides a key platform for nursing students to articulate the profession